REPRESENTATION OF RASTAFARIAN IDENTITY: A Textual Analysis Of Selected Lyrics From Bob Marley's Songs - Mega Noviandari, - (2011)
Entitled Representation of Rastafarian Identity (A Textual Analysis of Selected Lyrics from Bob Marley's Songs), the present paper is about the analysis of selected song lyrics written by Bob Marley with the employment of Woodward's theory of Identity and Difference. The analysis is directed to disclose Rastafarian identity as evidenced in the text. By employing a descriptive and qualitative case study method, it is found that Rastafarian identity is represented by suffering. The suffering is built from social issues that are evidenced from the analysis of connotative and denotative meaning in figurative languages applied in the lyrics. From the findings it can be concluded that Rastafarian issues carries universal meaning that voices the importance of freedom as well as humanity in life.